(untitled) (Journal of Ideas in Health, 2024)
Background: Toxoplasma gondii, is an intracellular protozoan parasite that relies on both definitive and intermediate hosts, such as rodents and pigs, for completion of its life cycle. Despite its public health importance, data on its infection in these hosts is limited in Tanzania, notably the Iringa region that had reported human mortalities due to toxoplasmosis. This study was undertaken to determine the seroprevalence and molecular detection of T. gondii in rodents and pigs in Iringa municipal. Methods: The study employed a cross-section design where 127 rodents and 240 pigs were sampled from selected wards in Iringa municipal from January 2023 to March 2023. For serological analysis, the antibody ELISA method was employed. Seropositive rodents and pigs were subjected to Nested PCR for T. gondii DNA detection using brain and blood samples from rodents and pigs, respectively. Results: Overall seroprevalence was 1.57% for rodents and 26.25% for pigs. Among the studied wards the highest proportion of Seropositive samples was from Kitwiru (6.25%) and Nduli (40%) for rodents and pigs, respectively. Statistical analysis indicated that Pigs aged 13-24 months were significantly more likely to test positive for anti-Toxoplasma IgG antibodies (p=0.0006), and antibody detection was strongly linked to hygiene practices in pig management (p < 0.0001). Additionally, in rodents, there was a statistically significant difference in exposure status related to species and collection site, with p-values of 0.043 and < 0.0001, respectively. T. gondii DNA was detected in 100% and 3.17% of seropositive rodents and pigs, respectively. Sequencing yielded one of each for rodents and pigs PCR positive samples respectively which showed about 98.36% to 99.15% similarity with T. gondii DNA from other countries isolated from different animal species. Conclusion: The detection of antibodies to T. gondii and subsequent identification of T. gondii DNA in samples from rodents and pigs indicate the public health significance of these animal species in the transmission of toxoplasmosis within the study region. Consequently, it is crucial to implement prevention and control measures in the studied animals to mitigate potential human exposure.